La estructura organizacional y su incidencia en el desempeño laboral de la Empresa Pública Municipal Gestión y Desarrollo E.P. - Pardo Quezada, Nixon Andrés (2023)
This research work aims to analyze the incidence of the organizational structure in the work performance of the Management and Development Municipal Public Company (Empresa Pública Municipal Gestión y Desarrollo E.P) of the city of Loja. The research problem focuses on analyzing the incidence of the organizational structure and management policies on the job performance of the employees of the Public Company, considering that the organization still works with an obsolete functional organic structure, initially defined in the Public Company Industrial Park of Loja, in which changes have not been considered to meet the new responsibilities assigned. A detailed analysis of the key concepts and results obtained is presented. For this, an exhaustive study has been carried out using data obtained from the collection of information from the surveys, two consistent, well-structured questionnaires in Likert scale format, applied to the employees of the organization and the stakeholders of the projects managed by the Public Company. To carry out the research, the quantitative approach of a non-experimental descriptive nature, with a cross-sectional cohort, was methodologically applied, allowing us to collect objective data through tools such as surveys, statistics, and data analysis, to examine and measure the results. The study findings revealed that the organizational structure has a weak positive relationship of 0.21% on job performance in the Public Company. However, there is a real relationship determined by the coefficient of determination, showing that the organizational structure influences job performance by 6.80%. Finally, a focused proposal capable of flexibly adapting to changes in the environment is presented to improve the organizational structure. To consider, the structure must be reviewed and updated periodically to ensure changes in the company